Chronic stress-induced neurodegenerative changes in Wistar rats: Hippocampal evidence and the mitigating effects of Allium Sativum - Opeyemi Adebola Adetunji; Adeola Oluwafunmbi Adegunle; Bayo Olufunso Adeoye; Joseph Chigbogu Nwobi; Oluseyi Sunday Fabiyi; Oyedayo Phillips Akano; Sanmi Tunde Ogunsanya; Samson Oluwole Oyewumi; Nnenna Linda Nwobi; Ayodeji David Adeoye; Olugbenga Olawole Olayinka (Babcock University Medical Journal, 2024)
Objective: Stress triggers a biological response perceiving a threat, chemicals and hormones surge throughout the body, after long-term exposure, stress accelerates cell ageing, immune senescence, and some age-related diseases such as neurodegenerative disorders and osteoporosis. This study finds possible effects of Allium sativum ethanolic extract on the hippocampus of chronic stress-induced neurodegenerative changes in male Wistar rats.